Relationships between circadian measures, depression, and response to antidepressant treatment: A preliminary investigation. (June 2017) - Swanson, Leslie M.; Burgess, Helen J.; Huntley, Edward D.; Bertram, Holli; Mooney, Ann; Zollars, Jennifer; Dopp, Richard; Hoffmann, Robert; Armitage, Roseanne; Todd Arnedt, J.
Abstract: Few studies have examined relationships between circadian rhythms and unipolar major depressive disorder. Further, no study to date has examined circadian markers as predictors of response to depression treatment. In the present study, we examined associations between circadian timing and its alignment with sleep and depression severity in 30 adults with major depressive disorder who completed a randomized controlled trial of two weeks of time in bed (TIB) restriction administered adjunctive to fluoxetine, with a focus on sex differences. Thirty adults with major depressive disorder received 8 weeks of fluoxetine 20–40 mgs and were randomized to 8 h TIB or 6 h TIB for the first 2 weeks. Participants in the 6 h TIB condition were further randomized to a delayed bedtime or advanced risetime group. Circadian measures included dim light melatonin onset (DLMO) and the difference between DLMO and midsleep point (i.e., phase angle difference). Depression was assessed using the Hamilton Rating Scale for Depression. For females, a phase delay after 2 weeks of fluoxetine and the experimental TIB manipulation was associated with a poorer response to fluoxetine, and depression severity was negatively correlated with phase angle difference, whereas males showed a positive correlation between depression severity and phase angle difference. Highlights: Circadian measures have not been studied in antidepressant treatment response. We examined circadian markers in a trial of repeated partial sleep deprivation to adjunctive to fluoxetine. A shorter phase angle difference was associated with more depression symptoms in females. A longer phase angle difference was associated with more depression symptoms in males. Phase delay was associated with poorer antidepressant response in females, but not males.